Alkaline Earth Cluster Compounds AE[W6I14] and the Solvate [Ca(C2H6SO)6][W6I14]. Issue 12 (11th June 2019) - Hummel, Thorsten; Moś‐Hummel, Agnieszka; Ströbele, Markus; Meyer, Hans‐Jürgen
Abstract : Alkaline earth tungsten iodide clusters AE [W6 I14 ] with AE = Mg, Ca, Sr, Ba and the solvated compound [Ca(C2 H6 SO)6 ][W6 I14 ] were prepared and structurally characterized. A new synthesis was employed, starting from W6 I22, which is an exceptional compound among binary tungsten iodides because it is soluble in common polar organic solvents. As evidence for the wide range of the applicability of W6 I22, we report the synthesis of the new AE [W6 I14 ] compounds in comparison to a solid‐state reaction departing from W3 I12 . Abstract :